A case of fresh fruits and vegetables supply chain performance improvement: a system dynamics modelling and analysis. (31st March 2023) - Ojha, Ravindra
Growth of agricultural food industry is critical to economy as it delivers the basic physiological necessity to human beings - food. Therefore, efficiency and effectiveness of fruits and vegetables supply chain (FVSC) has always attracted prominence. Motivation to this paper has been the live case of a food packaging industry - FoodFund located in London, Canada, which connects farmers to end-consumers through supply of fresh produce. Responsiveness, convenience, flexibility, affordability, product-freshness and sustainability in ecosystem are their six business pillars. In order to understand the key operational drivers and their inherent dynamics in FVSC, the author has applied value stream mapping (VSM) and system dynamics (SD) methodologies. The behavioural implications of the key drivers in FVSC were analysed using six SD based simulation scenarios. The dynamics amongst the four policy-drivers: fresh-produce procurement lead-time, packaging-velocity, finish-packed order dispatch-rate and transportation time to consumer, have provided useful insights for enhancing business growth and reducing variability in FVSC to the stakeholders.